Analysis Of Influence Of Service Quality And Facilities Of Room On Patients Satisfaction In Hospitals - Inun Nur Rochma; Karim Budiono; Zainulloh Zainulloh (ABM: International Journal of Administration, Business and Management, 2019)
This research aim to determine whether the patient is satisfied with the services and health facilities that were provided by the hospitals in and determine what factors are influential in dtermining the level of patient satisfaction to services and facilities provided by the hospital yasmin. Design of the study is divided into three types, namely research exploratory, descriptive and explanatory. Research study kind of explanatory research because the goal is to explain the causal relationship between variables testing hipotesis result show that the variable of service quality and room facilities have a significant effect on patient satisfaction at Yasmin Hospital. Keywords: Quality of service, space facilities, patient satisfaction.